2020
DOI: 10.3906/mat-1909-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of dual curves and dual focal curves in dual Lorentzian spaceD31

Abstract: In this paper, we have introduced dual Lorentzian connection, bracket and curvature tensor on dual Lorentzian space D 3 1. We have studied a dual curve in different situations in dual Lorentzian space D 3 1 and have found Bishop Darboux vector and some relations according to this vector field, Bishop frame and focal curve of the present dual curve. It has been shown that Bishop Darboux vector has a similar amount in three different cases of a dual curve and the first dual focal curvature of the aforementioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The geometry of RS has been exceedingly utilized in computer-aided manufacturing (CAM), computer-aided geometric design (CAGD), and geometric modeling [1][2][3][4][5]. Nowadays, the assets of ruled surfaces and their applications have been researched in Euclidean and non-Euclidean spaces (see, e.g., [6][7][8][9][10][11][12][13]). One of the popularization comfortable manners to addressing the movement of line space appears to discover an attachment with this space and dual numbers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometry of RS has been exceedingly utilized in computer-aided manufacturing (CAM), computer-aided geometric design (CAGD), and geometric modeling [1][2][3][4][5]. Nowadays, the assets of ruled surfaces and their applications have been researched in Euclidean and non-Euclidean spaces (see, e.g., [6][7][8][9][10][11][12][13]). One of the popularization comfortable manners to addressing the movement of line space appears to discover an attachment with this space and dual numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an SL (T L) curve on S 2 1 matches T L (S L) RS at E 3 1 . Due to their dealings with engineering and physical sciences in Minkowski space, senior geometers and engineers have researched and acquired extensive ownership of ruled surfaces (see [6][7][8][9][10][11][12][13]).…”
Section: Introductionmentioning
confidence: 99%
“…Notable examples of such symmetric curves include the Bullet-nose curve (Hašek, 2020), Kampyle of Eudoxus (Miura et al, 2022), Butterfly curve (Yücesan & Tükel, 2020), Atriphtaloid Sushanta (Ghuku & Saha, 2019;Saha, 2019), and the Kappa curve studied by Karkucinska-Wieckowska et al (2022). These node-like and dual curves have garnered significant attention from researchers due to their intriguing characteristics (Gilani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Via the E. Study map in screw and dual number algebra, the set of all oriented lines in Euclidean 3-space E 3 is instantly attached to the set of points on the dual unit sphere in the dual 3-space D 3 . Further characteristics on the necessary essential registrations of the E. Study map and one-parameter dual spherical movement can be found in [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%